Numerical investigation and design of perforated aluminium alloy SHS and RHS columns. (15th November 2019) - Feng, Ran; Liu, Jiarui
Highlights: FEA was performed on perforated aluminium alloy SHS and RHS columns. FEM was verified to accurately simulate the strengths and behaviour of aluminium alloy SHS and RHS columns. Parametric study including 594 specimens was used to evaluate the effects of critical geometric parameters. EC9 is generally appropriate for imperforated aluminium alloy SHS and RHS columns. Proposed design equations are accurate for perforated aluminium alloy SHS and RHS columns. Abstract: This paper describes a numerical investigation on perforated aluminium alloy square and rectangular hollow section (SHS and RHS) columns by the finite-element analysis (FEA). The non-linear finite-element model (FEM) was developed by considering both geometric and material non-linearities. The initial local and overall geometric imperfections of aluminium alloy columns were incorporated in the FEM. The non-linear FEM was verified against the corresponding experimental results, which was further used for an extensive parametric study that consisted of 594 specimens with different cross-section dimensions, overall lengths, as well as diameters, numbers and locations of circular openings. The ultimate strengths of the columns obtained from FEA were employed to evaluate the current design specifications for aluminium alloy and cold-formed steel structures. It is demonstrated that American Specification (AA) and limit state design (LSD) in Australian/New Zealand Standard (AS/NZS) are somewhat unconservative, whereas allowable stress design (ASD) in Australian/New Zealand Standard (AS/NZS) and Chinese Code are quite conservative, while European Code (EC9) is generally appropriate for imperforated aluminium alloy columns. In addition, North American Specification (NAS) and direct strength method (DSM) for cold-formed steel structural members with openings are quite conservative for aluminium alloy columns with circular openings. The design equations proposed based on the design rules of EC9 were verified to be accurate for perforated aluminium alloy SHS and RHS columns under axial compression.